(3YbdGA GdeLGfjfs - (3GdMSf Hf eMeO Hf MHjH Hf CjhH CHh GdbGSe GdfjSGHhQj,J (B406 (3g` s
(3ChdgG (B:s
(3CeG HYO, aTQa GdEfSGf haVjdJg GdJj HgG aGb LedI ef CUfGa GdNdb HbdHg s
(3BNQgG (B:s
(3hbO hba Ydi GdMSjf Hf efUhQ, hYdi QCSg ONhdg, abGd dg GdMSjf(B: (3TgOJ GdfGQ hGdLf` `I hGdCedGc hGdcQSj Je GdcJGH s
(3GdhQbI GdChdi hGdCNjQI Hbde eJCNQs
(3fhGOQ hCTYGQ hCNHGQ Yf GdMebi hGdeLGfjf ef GdPchQ hGdEfGKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B213s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B44 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs